Bing–Neel Syndrome: An Unknown GCA Mimicker - Arifa Javed; Sadia Arooj Javed; Barbara Ostrov; Jiang Qian; Khoa Ngo (Case Reports in Rheumatology)
Giant cell arteritis (GCA) is a chronic granulomatous vasculitis of medium and large arteries leading to cranial and extracranial manifestations. Temporal artery biopsy is considered the gold standard; however, its sensitivity is low at 47%. We report a unique case of Bing–Neel Syndrome (BNS) presenting as biopsy-proven GCA. BNS is a rare complication (1%) of Waldenstrom Macroglobulinemia (WM), which results from infiltration of lymph plasmacytoid cells and plasma cells into the central nervous system. A 77-year-old female with a past medical history of glaucoma, hypertension, diabetes, and chronic ocular ischemic syndrome in her right eye presented with progressive left eye vision loss for 5 days. Fundoscopic examination was notable for pseudophakic pseudopallor but no optic disc edema. Intraocular pressure was >40 and normalized after acetazolamide. The patient was started on pulse dose steroids by her neuro-ophthalmologist. She was discharged home on 60 mg of prednisone. At follow up with her neuro-ophthalmologist, new dot blot hemorrhages in the left eye were noted and she was readmitted for pulse dose of intravenous methylprednisolone. Temporal artery biopsy was consistent with GCA spectrum. Work up revealed paraproteinemia and subsequent bone marrow biopsy demonstrated WM. The patient was treated for her WM and her ophthalmic complications stabilized.